2020
DOI: 10.33830/jom.v16i1.785.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Crude Oil Price Shocks on Indonesia Stock Market Performance

Abstract: The main purpose of this study is to observe the effects of the crude oil price shocks on Indonesia stock market performance to complete the literature on Indonesia stock market behavior. We examined the effects of the crude oil price shocks on Indonesia stock market performance through the cointegration relationship mechanism between IHSG and the crude oil price and between IHSG and the global stock market indices. The Brent crude oil price data taken from FRED economic data, the Federal Reserve Bank of St.Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…As an importing country, when the oil price rises, it will be followed by increased production costs, so that the price charged is also more expensive, the people's income will be used up to buy basic goods, people will be reluctant to invest, as a result, the Composite Stock Price Index will decrease. This finding is supported by Darmawan et al (2020) and Adam et al (2015) that the price of crude oil with the Composite Stock Price Index is cointegrated. The price of crude oil does not have a short-term equilibrium relationship which implies that an increase or decrease in the price of government oil in the short term cannot affect the Composite Stock Price Index.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…As an importing country, when the oil price rises, it will be followed by increased production costs, so that the price charged is also more expensive, the people's income will be used up to buy basic goods, people will be reluctant to invest, as a result, the Composite Stock Price Index will decrease. This finding is supported by Darmawan et al (2020) and Adam et al (2015) that the price of crude oil with the Composite Stock Price Index is cointegrated. The price of crude oil does not have a short-term equilibrium relationship which implies that an increase or decrease in the price of government oil in the short term cannot affect the Composite Stock Price Index.…”
Section: Discussionsupporting
confidence: 63%
“…The price of the product also increases and people are unwilling to invest (Adam et al, 2015). Cointegration of Composite Stock Price Index and oil prices support by Adam et al (2015) and Darmawan et al (2020). However, Hersugondo et al (2015) argues that the price of oil does n't have a cointegration with the Composite Stock Price Index.…”
Section: Crude Oil Pricementioning
confidence: 94%
See 1 more Smart Citation
“…This process is always directed at the development of a bureaucratic figure with clear, complete, efficient, effective, responsible, open and accessible duties and responsibilities, which is interwoven with one another as a unified and consistent bureaucracy. According to Darmawan et al (2020) and Hasibuan (2013), work procedures need to be oriented to impersonal criteria and mechanisms that are directed through the application of excellent service with increased quality of organizational performance, efficiency, social welfare, and creativity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Salles et al (2022) presented evidence of the influence of crude oil prices on the stock markets of 18 countries, demonstrating diverse impacts across these economies. Furthermore, Darmawan et al (2020) revealed that fluctuations in crude oil prices hurt the stock market performance of oil-importing countries like Indonesia (R. Robiyanto, 2018;Robiyanto Robiyanto, Santoso, Atahau, & Harijono, 2019;Salisu & Isah, 2017), but a positive effect on oil-exporting countries, emphasizing differential impacts based on the economic status of these nations (Darmawan et al, 2020). This finding is further supported by Zaman (2019), who highlighted the impacts of oil price fluctuations on various economic aspects, including money markets, exchange rates, economic growth, and international trade between oil-importing and oil-exporting countries.…”
Section: Crude Oil Prices and Sharia Stock Marketmentioning
confidence: 99%